Another Piece of the Puzzle : Adding Swift Data on Documentary Collections to the Short-Term Forecast of World Trade - Ghazaryan, Narek (IMF Working Papers; Working Paper ;, 2021)
This paper extends earlier research by adding SWIFT data on documentary collections to the short-term forecast of international trade. While SWIFT documentary collections accounted for just over one percent of world trade financing in 2020, they have strong explanatory power to forecast world trade and national trade in selected economies. The informational content from documentary collections helps improve the forecast of world trade, while a horse race with machine learning algorithms shows significant non-linearities between trade and its determinants during the Covid-19 pandemic.